Spermatic cord lipoma and its clinical significance - Gandhi, Chinmay S. (International Surgery Journal, 2025)
Cord lipoma is frequently seen during open inguinal hernia surgery. Author has selected three of his cases for discussion. These three cases represent various clinical presentations in which cord lipoma can cause recurrence, pseudo recurrence and inguinal pain. Author like to discuss clinical presentation, investigation and management of cord lipoma. This will help surgeons to know clinical significance of spermatic cord lipoma.